Analysis of dedicated and shared device‐to‐device communication in cellular networks over Nakagami‐m fading channels. Issue 10 (26th July 2017) - Joshi, Sandeep; Mallik, Ranjan K.
Abstract : Device‐to‐device (D2D) communication, unlike conventional cellular communication, is described as the direct communication between devices bypassing the network infrastructure. This mode of direct communication, due to its advantages, is being proposed as an integral part of the next generation cellular networks with the additional interference between the users being a challenge. In this study, the authors develop an analytical framework for a D2D‐enabled downlink cellular network with Nakagami‐ m fading between the D2D communication links. The authors derive tractable expressions for the coverage probability of D2D links and cellular users, considering different propagation conditions experienced by D2D and cellular links. Using stochastic geometry, the authors provide the coverage probability analysis for the dedicated network, having orthogonal frequency resource allocation, and for the shared network, where the frequency resources are reused. Furthermore, the authors extend the coverage probability analysis to include interference‐limited dedicated and shared networks. Numerical results corroborate their analysis. The authors also derive the expressions for ergodic spectral efficiency of D2D links for both dedicated and shared networks. The results obtained are helpful in understanding the system behaviour and show the dependence of network performance on the system parameters.